Agricultural extension in developing countries - Adams, M. E. (Burnt Mill, Harlow, Essex : Longman, 1982)
This book, intended for students of extension of diploma, undergraduate or postgraduate level, as well as for planners and field workers, maps out a fresh approach to the subject.
Includes bibliographical references and index.
osa 29/01/2019
Loans
Keywords: Agricultural extension work; Developing countries